2017
DOI: 10.1021/acs.energyfuels.6b02638
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Atomic Potassium in Plumes over Burning Solid Fuels Using Infrared-Diode Laser Spectroscopy

Abstract: Solid fuels, such as coal and biomass, comprise a large portion of the current annual world energy supply, roughly equal to the annual oil consumption. During solid fuel combustion, certain species, though they are fairly benign outside of the combustion system, can cause damage in and around the combustion chamber. Alkali release from coal and biomass is known to cause severe problems in solid fuel fired boilers, such as fouling and corrosion of the heat transfer surfaces. In this work, the amount of atomic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…The distribution of K(g) and KOH(g) in the plume resembled a Gaussian shape, from which the path length was estimated to 20 ± 1 mm. This is in accordance with [21], where pellets of similar size were used as point sources of K(g).…”
supporting
confidence: 75%
“…The distribution of K(g) and KOH(g) in the plume resembled a Gaussian shape, from which the path length was estimated to 20 ± 1 mm. This is in accordance with [21], where pellets of similar size were used as point sources of K(g).…”
supporting
confidence: 75%
“…The concentration of K atoms was measured using the TDLAS system, based on the Beer–Lambert law: 7,16,33,34 where ν is the frequency of the light, I 0 (ν) and I (ν) are the intensity of the light before and after passing through the absorbers, respectively, and I n and I e are the frequency-independent backgrounds from the detector dark current and broadband emission, respectively. It was found that the broadband emission I e from the investigated methane flames was negligible, especially as our detector was placed ∼1.5 m away from the flame and an aperture was used in the beam path.…”
Section: Methodsmentioning
confidence: 99%
“…I n was assumed to be constant and obtained under the condition without laser beam in the flame. The frequency-dependent absorbance, α(ν), is proportional to the optical path length L and the number density N of K atoms: 7,35 where σ(ν) is the absorption cross section at frequency ν, which can be expressed aswhere h is the Planck’s constant, ν 0 the central frequency, B 12 the Einstein absorption coefficient, c the speed of light, χ(ν, N , T ) the area-normalized line shape function, and T the temperature. The line shape function can be described by a Voigt profile in the atmospheric environment.…”
Section: Methodsmentioning
confidence: 99%
“…Weng et al [15] measured the release of atomic potassium from burning coal, wood, and straw pellets using tunable diode laser absorption spectroscopy (TDLAS). Qu et al [16] used the same technique to simultaneously measure the flame temperature, water vapor and atomic potassium distribution during entrained-flow biomass combustion and they observed that potassium species rapidly undergo primary ash transformation reactions even if the fuel particles reside in an oxygen-deficient environment.…”
Section: Introductionmentioning
confidence: 99%